Pengembangan Aplikasi Untuk Membantu Dalam Penyusunan Dokumen Menggunakan Android - Tanto Johan Wahono; Agustinus Noertjahyana; Lily Puspa Dewi (Jurnal Infra, 2017)
Nowadays, many peoples need mobile device as an application for saving many documents. Usually, the documents scattered in various folders at different location with unstructured documents’ name. It causes difficulty of finding the documents. Furthermore, peoples need to open the document in various format (pdf, ppt, pptx, doc, docx). There’s condition when they just need to save some document pages to their mobile device.This application is made for mobile device’s users that developed with Android Studio and Notepad++. It can display the content of the document in some format (pdf, ppt, pptx, doc, docx) and combine the content from one document to another. Moreover, it can make a new document that contain some pages from other document. Users also can search the title and word in the document.According to the implementation result which has been tested on Android 5 (Lollipop), this application was able to show the result from open document, new document, merge document, tittle search, and word search by phonegap.